2023
DOI: 10.1093/jas/skac295
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a molasses-based liquid supplement on gastrointestinal tract barrier function, inflammation, and performance of newly received feedlot cattle before and after a transport stress

Abstract: The objective of this study was to determine the effect of a dry versus a molasses-based liquid supplement on ruminal butyrate concentration, gastrointestinal tract (GIT) barrier function, inflammatory status, and performance of newly received feedlot cattle. In experiment 1, 60 mixed breed steers (234 ± 2.1 kg) were weaned, held overnight at a sale barn, then transported 14 h to Purdue University. After arrival, steers were weighed, blocked by body weight, and allotted within block to treatments (six pens per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Higher levels of inflammatory mediators, including proinflammatory cytokines IL-1β, TNF-α, and IL-6, are common phenotypes of cardiac inflammation and the main factors that cause inflammatory damage ( Quagliariello et al, 2021 ). A previous study demonstrated that IL-1β, TNF-α, and IL-6 were promoted in cattle after TS lasting for 6 h, suggesting that TS can aggravate the inflammatory response of animals ( Silva et al, 2023 ). In the present study, to further confirm that TS induces cardiac injury by triggering sterile inflammation and the anti-inflammatory effect of APS, we detected the levels of these proinflammatory factors and IFN-β.…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels of inflammatory mediators, including proinflammatory cytokines IL-1β, TNF-α, and IL-6, are common phenotypes of cardiac inflammation and the main factors that cause inflammatory damage ( Quagliariello et al, 2021 ). A previous study demonstrated that IL-1β, TNF-α, and IL-6 were promoted in cattle after TS lasting for 6 h, suggesting that TS can aggravate the inflammatory response of animals ( Silva et al, 2023 ). In the present study, to further confirm that TS induces cardiac injury by triggering sterile inflammation and the anti-inflammatory effect of APS, we detected the levels of these proinflammatory factors and IFN-β.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress in beef cattle, mainly induced by factors such as diet composition [ 14 , 15 ], rearing environment [ 16 ], and transportation [ 17 ], might be experienced throughout their growth and development, which could highly impair the growth performance and meat quality of beef cattle [ 14 ]. Current research on TAN in ruminants mainly focuses on methane (CH 4 ) emission [ 5 ] and nitrogen utilization [ 5 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…To enhance management strategies that improve animal health and well-being ( Beenken-Bobb et al, 2023 ; Dornbach et al, 2023 ; Gouvêa et al, 2023 ; Rients et al, 2023 ; Silva et al, 2023 ).…”
mentioning
confidence: 99%